Atención y prevención odontológica en pacientes embarazadas. - Arias Moncayo, Victoria Abigail (2024)
This research work aims to analyze the importance of dental care and prevention in pregnant patients, identify the most common oral diseases during pregnancy, determine control and prevention measures, and point out the physiological changes of the pregnant woman through a scientific bibliographic review, which was based on the PRISMA method. For its preparation, bibliographic sources were taken from journals indexed in scientific databases such as PubMed, Scielo, Medigraphic, Elsevier, and Google Scholar. These studies were published between 2016 and 2023, from which 65 scientific articles were obtained; they went through evaluation indices such as the Average Count Citation (ACC) and Scimago Journal Ranking (SJR) that guarantee their academic significance. It was determined that dental care and prevention in pregnant patients is crucial because it will help the mother have optimal oral health, and thus there are no severe consequences for the development and life of the child, and that the most common oral diseases during pregnancy are caries, dental erosion, pyogenic granuloma, xerostomia, gingivitis, periodontitis, hyperemesis gravidarum, and gastric reflux. In addition, adequate control and prevention measures are periodic consultations with the professional to identify risk factors for developing oral diseases. It was identified that the excessive release of hormones such as chorionic gonadotropin, progesterone, estrogen, proinflammatory cytokines, and prostaglandins such as IL1β, IL-6, TNF-α, and PGE2 produces the most common physiological changes in pregnant patients.